Relationship of Physical Change and Social Culture with the Risk of Eating Disorder in One of Surabaya High School - Gibrata, Aisyah Alhaura; Kalalo , Royke Tony; Febriyana, Nining; Irawan, Roedi (Jurnal Psikiatri Surabaya, 2024)
Introduction: Adolescents aged 10 to 19 experience significant growth in various areas. Around 14% of them struggle with mental health, and eating disorders have the highest mortality rate. According to research, screen-related disordered eating affects about 1 in 8 high school students, and sociocultural pressure is positively associated with bulimia-related behaviors. Limited data on physical changes and sociocultural influences on eating disorders exist in Surabaya, Indonesia. The study aims to examine the potential correlation between physical alterations and sociocultural elements and the likelihood of eating disorders in one of Surabaya’s high schools. Methods: This cross-sectional observational analytic study collects primary data using two questionnaire instruments: EAT-26e collected samples from 60 students in SMAN2 Surabaya and SATAQ-4 using random stratified sampling. We used random stratified sampling to collect samples from 60 students in one of Surabaya’s high schools. We used SPSS version 25 to examine the data using the Spearman’s Rho Correlation Coefficient. Results: Physical changes show no significant correlation; in contrast, sociocultural pressure results show a significant correlation with the risk of eating disorders. Peer pressure, family pressure, and media pressure do not significantly influence the subscales of social culture under measurement. Conclusion: In one of Surabaya’s high schools, there is a significant positive correlation between sociocultural factors and the risk of eating disorders; however, there is no significant correlation between physical changes and the risk of eating disorders.